Building Jetties to the Future: Thinking and Doing Social Work in a 'moment of Danger.' - Susan P. Kemp (Social Work and Society)
This paper engages the core question animating the 2021 Social Work Futures conference: What 'social work' does the world need now, and in the years to come? It argues that while the profession's mandate to respond to the human needs and social issues in front of it cannot be sidestepped, present-focused interventions are not in themselves sufficient. The entangled 'wicked problems' confronting global communities - such as climate change, poverty and inequality, homelessness, or zoonotic pandemics - are complex, contingent, and intransigent. Addressing them demands forward-looking, transformational thinking and action, within and across disciplines. How can - or should - social work position itself in relation to these realities? Can the profession balance responsiveness in the present while also fundamentally re-orienting its knowledge systems and practices? The paper engages these critical but vexing questions through the lens of arguably the most profound global challenge of this era: climate change and the interlocking socio-environmental challenges related to and contributing to it, and suggests some potential pathways for transforming social work knowledges, practices, and capacities toward becoming a discipline of consequence in an increasingly contingent, unstable, and unsustainable world.